First European quality of life survey social dimensions of housing - Domanski, Henryk.; Ostrowska, Antonina.; Przybysz, Dariusz.; European Foundation for the improvement of living and working conditions. (Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2006)
A good standard of housing is, along with level of income, an essential component of quality of life and a valid indicator of the material conditions of a household. In fact, having one's own personal space - an intimate sphere in which someone can regenerate and escape from the bustle of everyday life - is one of the most fundamental biological, psychological and social needs. It is necessary for family well-being, and crucial for raising children and for their socialisation. Ultimately, it is a place for rest and relaxation in which people spend a significant part of their everyday lives.